Initiation of cavitation upon drawing of pre-oriented polypropylene film: In situ SAXS and WAXD studies. (16th October 2017) - Xiong, Bijin; Kang, Jian; Chen, Ran; Men, Yongfeng
Abstract: Initiation of cavitation upon drawing of pre-oriented polypropylene films has been investigated via in-situ small angle X-ray scattering (SAXS) and wide angle X-ray diffraction (WAXD) techniques. The macroscopic strains for the initiation of the cavitation εcav and for the initiation of crystal shear εcs have been estimated from in-situ SAXS and WAXD tests respectively. Local crystal shear appears before cavitation upon drawing in machine direction (MD) has been revealed via comparison of εcs and εcav . The initial size of the cavities in MD is larger than the long period of crystalline lamellae while the size in transverse direction is inversely proportional to the relative fraction of daughter lamellae. Macroscopic critical stresses for the initiation of cavitation σcav and for the initiation of crystal shear σcs have been estimated as well. The critical stress σcav is independent on the crystallinity, whereas σcs increases with increasing crystallinity. The mechanism for the initiation of cavitation has been proposed, i.e. the cavitation is initiated by the breakage of crystalline lamellae at the anchor point of the daughter lamellae. Graphical abstract: Highlights: Initiation of cavitation upon drawing of pre-oriented polypropylene was studied. Competition relation between cavitation and crystal shear was observed. Cavitation initiated at the anchor point of daughter lamellae was proposed.